PENERAPAN METODE TANYA JAWAB UNTUK MENINGKATKAN PARTISIPASI SISWA DALAM PEMBELAJARAN IPA DI KELAS III SD - Dini Alya; Ifdah Aulia; Nofeni Ramadani; Nabila Anastasya; Andi Gusmaulia Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effectiveness of the implementation of the question-and-answer method in improving student participation in science learning in Class III of SD N 40/I Bajubang Laut. The background of this study was the low level of student participation in science learning, which was still dominated by the lecture method, causing students to become passive and less involved in the learning process. This study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart spiral model, which consists of planning, action, observation, and reflection stages conducted in two cycles. The research subjects consisted of 20 students, including 8 male students and 12 female students. Data collection techniques included observation, interviews, and documentation. The results showed that the implementation of the question-and-answer method significantly improved student participation. The average student participation increased from 30.9% in the pre-cycle stage to 53.6% in Cycle I and further increased to 81.8% in Cycle II. In addition, student learning mastery also improved from 35.4% in the pre-cycle stage to 85.4% in Cycle II. The findings indicate that the structured implementation of the question-and-answer method, accompanied by the use of simple questions, think time, reinforcement, and concrete media, was effective in creating active, interactive, and meaningful science learning. Therefore, the question-and-answer method can be used as an alternative teaching method to improve student participation and learning outcomes in elementary school science learning